Association between anthropometry, upper extremity strength, and sprint and endurance paddling performance in competitive and recreational surfers - Coyne, J. O. C.; Tran, T. T.; Secomb, J. L.; Lundgren, L.; Farley, O. R. L.; Newton, R. U.; Sheppard, J. M. (International Journal of Sports Science & Coaching, 2016)
This study investigated the correlations with anthropometry, upper extremity strength, and surfboard paddling performance in recreational and competitive surfers. Twenty-nine recreational and competitive male surfers were assessed for height, mass, relative arm span, relative seated height, relative biacromial width, and skinfolds (Sum7). The upper extremity strength variables assessed were the relative 1RM pull up and 1RM dip. The surfboard paddling variables assessed were a 15m sprint-paddling test and a 400m endurance-paddling water-based test. Pearson correlation analysis and independent t-tests were used to compare differences between groups and determine the significant correlations between variables. Sum7 and relative arm span were correlated with speed in all paddling efforts meanwhile the sprint-paddling ability was correlated with the upper extremity strength. Significant differences between competitive and recreational surfers exist in relative arm span and endurance paddle performance. The strong relationships between the physical variables can be used by sports coaches and support staff to influence talent identification, training, and nutrition programs. ABSTRACT FROM AUTHOR